Evaluation of MRI/Ultrasound Fusion-Guided Prostate Biopsy Using Transrectal and Transperineal Approaches. (28th September 2017) - Tewes, Susanne; Peters, Inga; Tiemeyer, Ansgar; Peperhove, Matti; Hartung, Dagmar; Pertschy, Stefanie; Kuczyk, Markus A.; Wacker, Frank; Hueper, Katja
Abstract : Purpose . To evaluate transrectal (TR) and transperineal (TP) approaches for MRI/ultrasound (MRI/US) fusion-guided biopsy to detect prostate cancer (PCa). Materials and Methods . 154 men underwent multiparametric MRI and MRI/US fusion-guided biopsy between July 2012 and October 2016. 79/154 patients were biopsied with a TR approach and 75/154 with a TP approach. MRI was retrospectively analyzed according to PI-RADS version 2. PI-RADS scores were compared with histopathological results. Descriptive statistics, accuracy, and negative and positive predictive values were calculated. Histopathological results of first, second, and third MRI targeted biopsy cores were compared to evaluate the impact of one verus multiple targeted cores. Results . Detection rates of PCa were 39% for TR biopsy and 75% for TP biopsy. Sensitivity/specificity for tumor detection with PI-RADS ≥ 4 were 81/69% for TR biopsy and 86/84% for TP biopsy. In 31% for TR biopsy and 19% for TP biopsy, PCa was found in the second or third MRI targeted biopsy core only. Conclusion . MRI/US fusion-guided biopsy may be conducted with the TR as well as the TP approach with high accuracy, giving more flexibility for diagnosis and the option for focal treatment of PCa.